THE DETERMINANTS ON DEBT POLICY AND THE RELATIONSHIP BETWEEN THE FACTORS ON DEVELOPMENT SUSTAINABILITY ISSUES IN AN EMERGING ECONOMY - Siagian, Pariang (Strategic Management Business Journal, 2024)
Research background: Indonesian government debt has become protruding into the political circle, making many parties, including academics, overwhelming the nation's future economy. This study examines the determinants of debt policy and their impact on development sustainability. Purpose of the article: The result reveals that some independent variables have a considerable effect on dependent variables, namely tax ratio to debt ratio, deficit and tax ratio to economic growth, deficit to per capita income, tax ratio to inequality, tax ratio to HDI, and deficit and tax ratio to asset growth. Meanwhile, the others have no statistical effects on each dependent variable, like the deficit to debt ratio, debt ratio to economic growth, tax ratio and debt ratio to per capita income, deficit and debt ratio to inequality, deficit and debt ratio to HDI, and debt ratio to asset growth. Methods: A multivariate regression model was constructed by using panel data regressions to evaluate the relationship between these factors and development sustainability for the period 2005–2022. Findings & value added: The research results can be used to identify why some factors determine elements of sustainable development while others do not. The implication, the government prefers certain discretion in order to enhance debt policy and maintain sustainable economic development, for which the most prudent mitigation and solution at every step that can elevate and solve the problem of the barriers. JEL Classification: M2, M4, M41